Implementation of the Design Thinking Method in Optimizing the UI/UX of the Maxim Application - Salsabilla Destari; Ica Admirani; Meiyi Darlies (Jurnal Komputer, Informasi dan Teknologi, 2024)
The Maxim application faces low user satisfaction, particularly in terms of ease of navigation and feature access speed. The average user satisfaction with ease of navigation before the improvements was 53.44%, while satisfaction with feature access speed reached only 52.43%. This study aims to improve the quality of the user interface (UI) and user experience (UX) by applying the Design Thinking method. This method involves five stages empathize, define, ideate, prototype, and test, which are used to identify problems, design solutions, and test the results of the improvements. Data were collected through interviews, questionnaires, and user reviews on Playstore, which were then evaluated using A/B testing with 100 respondents. The results showed that after the improvements, user satisfaction with ease of navigation increased to 73.77%, while feature access speed increased to 73.00%. Therefore, the application of the Design Thinking method successfully enhanced both the ease of use and the speed of feature access in the Maxim application.